2022
DOI: 10.1007/s11240-022-02237-0
|View full text |Cite
|
Sign up to set email alerts
|

In vitro regeneration of Piper longum L. and comparative RP-HPLC analysis of piperine production of in vitro and in vivo grown plants

Abstract: Piper longum L. is a well known spice plant belonging to the family Piperaceae with high pharmacognosy potential, but it is becoming threatened due to overexploitation. Thus, this investigation aims to standardize a cost effective protocol for in vitro propagation of this economically important plant.Internodal segments were used as explant for callogenesis in Murashige and Skoog medium with 3% sucrose and 0.8% agar, with NAA or 2,4 D. Optimum callus induction was observed in MS medium with 5.0 mg/L NAA. Calli… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 21 publications
(15 reference statements)
1
1
0
Order By: Relevance
“…These results agree with Xiong et al [28], where the high concentration of NAA and BAP in combination enhanced callus growth in Cordia subcordata. In addition, high NAA concentrations were used successfully in promoting callus growth in Piper longum [29]. In another study, Daffalla et al [30] found that a combination of 10.74 µM NAA with 6.66 µM BAP increased the callus growth of Grewia tenax, and this is in general agreement with the results of this study.…”
Section: Gileadensis Callus Culturesupporting
confidence: 91%
“…These results agree with Xiong et al [28], where the high concentration of NAA and BAP in combination enhanced callus growth in Cordia subcordata. In addition, high NAA concentrations were used successfully in promoting callus growth in Piper longum [29]. In another study, Daffalla et al [30] found that a combination of 10.74 µM NAA with 6.66 µM BAP increased the callus growth of Grewia tenax, and this is in general agreement with the results of this study.…”
Section: Gileadensis Callus Culturesupporting
confidence: 91%
“…These propagated materials, with or without elicitors, can be utilized to extract bioactive compounds. Fruits of in vitro grown plants of Piper longum and cell suspensions of Cnidoscolus chayamansa showed greater contents of piperine and lupeol acetate than in vivo plants, respectively [ 17 , 18 ]. There is a report that investigated the in vitro production of betacyanin from pokeweed cell suspension [ 19 ].…”
Section: Introductionmentioning
confidence: 99%